Disease causing property analyzation of variants in 12 Chinese families with polycystic kidney disease. Issue 11 (24th September 2020) - Dong, Kexian; Liu, Xiaogang; Jia, Xueyuan; Miao, Huanhuan; Ji, Wei; Wu, Jie; Huang, Yun; Xu, Lidan; Zhang, Xuelong; Su, Hui; Ji, Guohua; Liu, Peng; et al.
Abstract: Background: Polycystic kidney disease (PKD) is an inherited disease that is life‐threatening. Multiple cysts are present in the bilateral kidneys of PKD patients. The progressively enlarged cysts cause structural damage and loss of kidney function. Methods: This study examined and analyzed 12 families with polycystic kidney disease. Whole exome sequencing (WES) or whole genome sequencing (WGS) of the probands was performed to detect the pathogenic genes. The candidate gene segments for lineal consanguinity in the family were amplified by the nest PCR followed by Sanger sequencing. The variants were assessed by pathogenic and conservational property prediction analysis and interpreted according to the American College of Medical Genetics and Genomics. Results: Nine of the 12 pedigrees were identified the disease causing variants. Among them, four novel variants in PKD1, c.6930delG:p.C2311Vfs*3, c.1216T>C:p.C406R, c.8548T>C:p.S2850P, and c.3865G>A:p.V1289M (NM_001009944.2) were detected. After assessment, the four novel variants were considered to be pathogenic variants and cause autosomal dominant polycystic kidney disease in family. The detected variants were interpreted. Conclusion: The four novel variants in PKD1, c.6930delG:p.C2311Vfs*3, c.1216T>C:p.C406R, c.8548T>C:p.S2850P, and c.3865G>A:p.V1289M (NM_001009944.2) are pathogenic variants and cause autosomal dominant polycystic kidney disease in family. Abstract : This study examined and analyzed 12 families with polycystic kidney disease using whole exome sequencing or whole genome sequencing and several prediction tools. After assessment and interpretion, the four novel variants were considered to be pathogenic variants and cause autosomal dominant polycystic kidney disease in family. The present study enriched the knowledge of the pathogenicity for autosomal dominant polycystic kidney disease and would improve the understanding of this autosomal dominant disorder.